The Impact of Office Relocation on Employee Productivity: A Case Study of Cirebon-Lombok - Jannah, Raodatul (Journal of Social Science and Education Research, 2024)
This study explores the impact of office relocation on employee productivity, focusing on the case of relocating a company’s office from Cirebon to Lombok. Utilizing a qualitative research approach, this study employs literature review and library research to examine how such relocations influence productivity levels. The research reviews relevant literature on office relocation, employee adaptation, and productivity metrics. It also analyzes the potential challenges and benefits that arise during the transition, including changes in the work environment, employee morale, and adjustment to new cultural and geographical contexts. Key findings suggest that the relocation process can have both positive and negative effects on productivity, depending on factors such as employee support, adaptation programs, and the suitability of the new location. The study highlights the importance of effective communication and strategic planning in minimizing disruptions and fostering a smooth transition. Furthermore, the analysis reveals that well-managed relocation processes can improve job satisfaction and motivation, leading to enhanced productivity. However, without adequate support, relocations may result in reduced morale and performance due to adjustment difficulties. The study provides recommendations for companies considering relocation to ensure that productivity is sustained or even improved throughout the process. The insights gained from this research can assist organizations in making informed decisions about office relocation and developing strategies to support their employees during such transitions.